THE VIABILITY OF HALAL FOOD INDUSTRY FOR BRUNEI ECONOMIC DIVERSIFICATION: SWOT ANALYSIS - Oh, Youri; Hamir, Ak Md Hisyamuddin bin Pg; Shah, Mohd Azwan Shah bin Mohd (PEOPLE: International Journal of Social Sciences, 2018)
There has been a growing interest in research for halal industry as the market has seen a tremendous growth in the global market and develops a strong presence in developed countries. With the halal industry being worth of US$1.2 trillion worldwide or US$650 billion alone in the food sector, vast opportunities in the global halal food industry for Brunei to use in order to diversify its economy. Brunei has been prioritised economic diversification as a mean to economic development; however, it has not shown any successful result so far. For a long period, Brunei has sustained its high dependency on oil and gas sector, in which economic diversification is a key to lower down the current dependency. Brunei Halal brand was established as one of attempts to help push forward Brunei's halal industry and supply the amount of halal certified food to the global Muslim population. In addition, owing to strong religious identity and principle, Brunei halal gained a reputable status to international and Islamic standards. The attempt of this paper is to assess the viability of the halal food industry as a source for economic diversification of Brunei with understanding of the current status of Brunei halal food industry by SWOT analysis. This study conducted semi-structured interview with respondents who are stakeholders in halal food industry to obtain further data in addition to data collected from secondary sources.